WTO 11th Ministerial Conference – Buenos Aires: contributions on market access - Rodriguez, Augustín Tejeda; Perini, Sofía C. (2017)
The Market Access pillar is one of the most significant in the WTO Agreement on Agriculture because of its magnitude and the impact of any change on agricultural trade rules. The reform of this pillar has not been possible since the Doha Round partly due to its ties to non-agricultural negotiations. The principle of single undertaking specified in that round of negotiations implies that virtually every item of the negotiation is part of a whole and indivisible package and cannot be agreed separately: “Nothing is agreed until everything is agreed”.